Sustainability standards and coffee exports from Tanzania - Evelyne A. Lazaro; Jeremiah Makindara; Fredy T. Kilima (Danish Institute for International Studies (DIIS), 2008)
One of the key trends characterizing agro-food trade in the last two decades has been the increas-ing complexity of public and private standards that are applied to imports into developed coun-tries. This paper aims to identify critical areas to facilitate compliance with sustainability standards in coffee, which is the major traditional export crop for Tanzania. Coffee experienced a dramatic downward trend in world market prices that led to a decreased contribution to foreign exchange earnings in producing countries in the early 2000s. Although prices have improved over the past few years, economies that are dependent on traditional agricultural exports such as coffee need strategies to ensure stability in export earnings. One of the possible venues for increased agri-cultural export value is through exports to niche markets, such as coffee that is certified against one or more sustainability certifications (e.g. Fair Trade, Utz Certified, Organic, and Rainforest Alliance). For this reason, a survey was conducted with key actors (producers, processors, and exporters) in the Tanzanian coffee sector to assess compliance to the Utz standard – the fastest growing sus-tainability standard in the coffee sector. This paper reviews the key trends in relation to sustain-ability standards in coffee, a profile of (and the main challenges faced by) producers that comply with the Utz standard in Tanzania, and the perceptions of those producers who have not yet attempted certification. It provides a first, qualitative, reading of the survey findings, which will be followed up by a more rigorous quantitative assessment of costs and benefits. The findings provided here show that so far only large-scale coffee producers have managed to meet the costs of compliance with the Utz standard in Tanzania; they also show that the rate of growth of Utz-certified coffee sales from Tanzania is quite low, even when compared with neighbouring Uganda and Kenya. High costs of certification and the perceived inadequateness of price premiums on certified coffee were identified as the most limiting factors against compliance. Strategic awareness creation and support services on coffee standards are required among all actors in the coffee sector in Tanzania to meet current consumer demands on social and environ-mental concerns. Therefore, the coffee sector regulatory system should provide an institutional guide on coffee standards. It should also stimulate discussion among smallholder organizations, such as farmer groups and primary cooperative societies, on whether Utz certification should be attempted. Continued research on sustainability standards is also needed to inform actors in the sector on critical emerging issues that affect demand, supply, and prices of coffee.
Keywords: 330; Kaffee; Export; Kaffeemarkt; Nachhaltige Entwicklung; Tansania